Reaching Byzantine Agreement in a Processor Fallible Virtual Subnet Network - Wang, S.C.; Yan, K.Q.; Zheng, G.Y.; Chih, C.T. (2006 Seventh International Conference on Parallel and Distributed Computing, Applications and Technologies (PDCAT'06), 2006)
Mobile ad-hoc network (MANET) is practical more and more due to it can provide processor joins to the network or leaves away anytime with non-infrastructure. Further, the fault-tolerance and reliability of the MANET has also been an important topic. The problem of reaching agreement in the distributed system is one of the most important issues to design a fault-tolerance system. In previous works, reach a common agreement among correct processors to cope with the influence from faulty components is significant in a fault-tolerance system. In this paper, the agreement problem is revisited in a MANET, which the processors maybe subject to malicious failure